Synthesis of phosphonate derivatives of 2'-deoxy-2'-fluorotetradialdose d-nucleosides and tetradialdose d-nucleosides - Lášek, Tomáš; Dobiáš, Juraj; Buděšínský, Miloš; Kozák, Jaroslav; Lapuníková, Barbora; Rosenberg, Ivan; Birkuš, Gabriel; Páv, Ondřej (Tetrahedron, 2021)
Analogs of nucleosides and nucleotides represent a promising pool of potential therapeutics. This work describes a new synthetic route leading to 2'-deoxy-2'-fluorotetradialdose D-nucleoside phosphonates. Moreover, a new universal synthetic route leading to tetradialdose d-nucleosides bearing purine nucleobases is also described. All new compounds were tested as triphosphate analogs for inhibitory potency against a variety of viral polymerases. The fluorinated nucleosides were transformed to phosphoramidate prodrugs and evaluated in cell cultures against various viruses including influenza and SARS-CoV-2.
Keywords: 2′-Fluoronucleoside; Tetradialdose d-nucleoside; Nucleoside phosphonate; Triphosphate; Prodrug